Rydberg Atoms and Strongly Coupled Atom-Light Systems - Zhang, Zihan (Transactions on Computer Science and Intelligent Systems Research, 2024)
Since the discovery of the Rydberg atom in 1885, research on the Rydberg atom has presented numerous discoveries about the Rydberg atom. As the atoms has valence electron in a high principal quantum number state, Rydberg atoms can interact with each other in a unique way, such as dipole-dipole interactions, Rydberg blockade and anti-blockade. To reach the Rydberg state, it is usually necessary to use a laser to excite the atoms from their ground state. Due to the special characteristics about Rydberg atoms as well as their interactions, it has demonstrated promising of application in different fields, for example, quantum computing and quantum information, as well as nonlinear optics and photonics. However, due to the technical limitations, the demand of deterministic atoms sources and the effect of blackbody radiation are still hindering the research relative to Rydberg atoms. For future study relative to Rydberg atoms, the additions with laser-trapping could be beneficial for fields like quantum electro dynamics and localized electromagnetic field probing.